PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS KEARIFAN LOKAL DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) SUB TEMA PERUBAHAN LINGKUNGAN UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - mulyani, sri (Journal Prakarsa Paedagogia, 2019)
AbstractThe purpose of this research and development is to develop and test the feasibility of a local wisdom-based worksheet using the CTL approach to improve the critical thinking skills of Grade V students. The research subjects are Grade V students of MI NU Imaduddin. This type of research is Research and Development (R And D). Data collection techniques use a questionnaire. The results showed that: (1) The development of local wisdom-based worksheets with a valid CTL approach based on validation from material experts, the media, and teachers. The eligibility criteria are 79% (feasible), 83% worth of content (very feasible), 72% worthiness (feasible), 75% linguistic worthiness (feasible), and 84% CTL assessment (very feasible). Based on the results of the validation and assessment that has been obtained, it can be concluded that the worksheet based on local wisdom is appropriate to be used as a source of student learning.Keywords: Worksheet, Local Wisdom, CTL, Critical Thinking Skills.Â